Diversity of rotavirus strains circulating in children under five years of age who presented with acute gastroenteritis before and after rotavirus vaccine introduction, University Teaching Hospital, Lusaka, Zambia, 2008–2015. Issue 47 (12th November 2018) - Simwaka, J.C.; Mpabalwani, Evans M.; Seheri, Mapaseka; Peenze, Ina; Monze, Mwaka; Matapo, Belem; Parashar, Umesh D.; Mufunda, Jacob; Mphahlele, Jeffrey M.; Tate, Jacqueline E.; Mwenda, Jason M.
Abstract: Background: Following the introduction of rotavirus vaccine into the routine immunization schedule, the burden of rotavirus disease has significantly reduced in Zambia. Although rotavirus vaccines appear to confer good cross-protection against both vaccine and non-vaccine strains, concerns about strain replacement following vaccine implementation remain. We describe the diversity of the circulating rotavirus strains before and after the Rotarix® vaccine was introduced in Lusaka from January 2012. Methods: Under five children were enrolled through active surveillance at University Teaching Hospital using a standardized WHO case investigation form. Stool samples were collected from children who presented with ≥3 loose stool in 24 h and were admitted to the hospital for acute gastroenteritis as a primary illness. Samples were tested for group A rotavirus antigen enzyme-linked immunosorbent assay. Randomly selected rotavirus positive samples were analysed by reverse transcription polymerase chain reaction for G and P genotyping and and Nucleotide sequencing was used to confirm some mixed infections. Results: A total of 4150 cases were enrolled and stool samples were collected from 4066 (98%) children between 2008 and 2011, before the vaccine was introduced. Rotavirus antigen was detected in 1561/4066 (38%). After vaccine introduction (2012 to 2015), 3168 cases were enrolled, 3092 (98%) samples were collected, and 977/3092 (32%) were positive for rotavirus. The most common G and P genotype combinations before vaccine introduction were G1P[8] (49%) in 2008; G12P[6] (24%) and G9P[8] (22%) in 2009; mixed rotavirus infections (32%) and G9P[8] (20%) in 2010, and G1P[6] (46%), G9P[6] (16%) and mixed infections (20%) in 2011. The predominant strains after vaccine introduction were G1P[8] (25%), G2P[4] (28%) and G2P[6] (23%) in 2012; G2P[4] (36%) and G2P[6] (44%) in 2013; G1P[8] (43%), G2P[4] (9%), and G2P[6] (24%) in 2014, while G2P[4] (54%) and G2P[6] (20%) continued to circulate in 2015. Conclusion: These continual changes in the predominant strains suggest natural secular variation in circulating rotavirus strains post-vaccine introduction. These findings highlight the need for ongoing surveillance to continue monitoring how vaccine use affects strain evolution over a longer period of time and assess any normal seasonal fluctuations of the rotavirus strains.